2018
DOI: 10.14202/vetworld.2018.990-1000
|View full text |Cite
|
Sign up to set email alerts
|

Modifications and optimization of manual methods for polymerase chain reaction and 16S rRNA gene sequencing quality community DNA extraction from goat rumen digesta

Abstract: Background and Aim:A critical prerequisite for studying rumen microbial community by high throughput molecular biology methods is good quality community DNA. Current methods of extraction use kits designed for samples from the different origin for rumen. This puts stress on the development of a relevant manual method for DNA extraction. The objective of this study was to modify the existing methods of community DNA extraction and thereby systematic comparison of their efficiency based on DNA yield, purity, 16S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…As a result, it is quick, simple, and inexpensive, and it may be used to isolate high-yield analytical grade DNA from gram-positive and gram-negative bacteria (Glenn, 2011). The author (Durgadevi A., 2018) there is a previous study on a modified method using fewer chemicals and techniques leading to PCR and the sequencing of 16S rRNA genes quality Isolation of DNA from Goat Rumen Digesta (Ali et al, 2021;Aphale et al, 2018;James et al, 2021). Following that, population DNA extracted using the boiling process approach could provide standard PCR amplification with general bacterial primers and specific bacterial 16S rRNA gene primers (Ahmed et al, 2017), demonstrating its suitability for a wide range of biological applications.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, it is quick, simple, and inexpensive, and it may be used to isolate high-yield analytical grade DNA from gram-positive and gram-negative bacteria (Glenn, 2011). The author (Durgadevi A., 2018) there is a previous study on a modified method using fewer chemicals and techniques leading to PCR and the sequencing of 16S rRNA genes quality Isolation of DNA from Goat Rumen Digesta (Ali et al, 2021;Aphale et al, 2018;James et al, 2021). Following that, population DNA extracted using the boiling process approach could provide standard PCR amplification with general bacterial primers and specific bacterial 16S rRNA gene primers (Ahmed et al, 2017), demonstrating its suitability for a wide range of biological applications.…”
Section: Resultsmentioning
confidence: 99%
“…Although it is difficult to directly compare the presence of SBSEC members in a single animal species due to the difficulties encountered over the years in the correct identification of SBSEC strains to the species (or subspecies) level by phenotypic and genotypic methods, the potential presence of S. lutetiensis (Previously classified as S. infantarius subsp. coli ) in domestic ruminants have been only addressed in caprine and their food products [ 57 , 58 ]. In this study, we also confirmed the presence of S. lutetiensis only in the rumen of Korean goats by direct isolation and sodA gene-based identification rather that from bovine, thus hypothesizing that the species might be one of the distinguished important commensal SBSEC in caprine.…”
Section: Discussionmentioning
confidence: 99%
“…These mitochondrial DNA sequences are unique and can be used as genetic markers for species identification. The 16S rRNA gene has been widely used for phylogenetic study and detection in other species [19][20][21][22]. It is expected that the nucleotide diversity of each cuscus species can be used as genetic markers and can determine the phylogenetic relationship of the cuscuses from Maluku and Papua.…”
Section: Introductionmentioning
confidence: 99%